Religions and Psychotherapies (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
The birth of modern psychotherapies$1 (Balong with the birth of psychology as a science on one side and with psychoanalysis, other depth-psychological treatments and behavioral therapies in addition to medical treatments of psychological disorders on the other side$1 (Bin the 19th and 20th centuries was accompanied by positivistic and mechanistic paradigms underlying empirical research and claims of scientific dignity [1]. Affirmations which could not be tested or observed empirically had to be excluded from science$1 (Bincluding any kind of metaphysics and religious belief, notwithstanding pioneering studies by William James [2], Granville Stanley Hall, James Henry Leuba and Edwin Diller Starbuck [3] for psychology in general and for psychology of religion(s) in particular. In particular, the critique of religions by Sigmund Freud has continuously exerted a strong impact in the fields of psychiatry and psychotherapies; in addition, regarding psychodynamics and symptoms of psychic disorders, religious phenomena in the lives of patients may be just as affected as other cognitive and emotional aspects and behaviors [4]. Consequently, religious experience and religious behavior of patients in psychiatry and psychotherapies have rarely been object of research and teaching apart from predominantly symptomatic and pathogenic perspectives. [...]s
English
Keywords: metapsychologies and religions; religiosity of patients and clinicians; religious values and psychotherapies; abstinence and neutrality in treatment; religious coping; religious interpretations of psychic disorders